Sprint canoe blade hydrodynamics - modeling and on-water measurement - Morgoch, D.; Galipeau, C.; Tullis, S. (Procedia Engineering, 2016)
A computational fluid dynamics model of the transient flow around a sprint canoe blade has been developed including the full blade motion in the catch and draw phases of the stroke, with the translational and rotational path of the blade is obtained from video analysis of a national team athlete. Examination of the blade path and associated flow patterns around the blade reveals the development of tip and side vortices and their interaction with the blade. An interval of reversed flow and pressure at the top of the blade late in the catch is seen and results in a braking pressure field on the blade surface. On-water measurements have also been made using a new instrumented paddle with multiple strain gauge full bridges. This level of bending moment measurement then allows the tracking of the real centre of pressure of the blade force and the determination of the real blade force (and its components) through the stroke.